Do Hospitals Respond to Increasing Prices by Supplying Fewer Services? - Salm, Martin; Wübker, Ansgar (My University, 2015)
Medical providers often have a significant influence on treatment decisions which they can use in their own financial interest. Classical models of supplier-induced demand predict that medical providers will supply fewer services if they face increasing prices. The authors test this prediction based on a reform of hospital financing in Germany. Uniquely, this reform changed the overall level of reimbursement - with increasing prices for some hospitals and decreasing prices for others - without affecting the relative prices for different types of patients. Based on administrative data, the authors find that hospitals do indeed react to increasing prices by reducing service supply.
Keywords: Krankenhaus; Gesundheitswesen; Finanzwesen; Gesundheitsversorgung; Kostensteigerung; Krankenhausfinanzierung